Desordenes temporomandibulares según índice de Helkimo y su relación con la sintomatología asociada y posición condilar en la población del distrito de moche 2007 - Aguirre Aguilar, Augusto Alberto (2008)
The present is a descriptive study of transversal cut, its purpose was to find existing relation between Signs and Symptoms of Temporomandibular Desorders (DTM) and Condilar Position using Helkimo index. It was made on 328 citizens of Moche district in Trujillo, Perú. Their ages oscillated from 18 to 80 years old, whom applied Helkimo Index , the card-index for associate symptomatology and Condilar position, executed activities by middle of auscultation and inspection. For determinate the existing relation between DTM , its variables and co-variables we used the single binarial regress logical test, to relate the bucal opening with age and sex co-variables was fulfill chi quadrate test. Finds show us, 67.5 % of DTM presence, been female sex the most afected with 81.03%, articulate noise 32.76% in its final phase, limited bucal opening in 49.43%, left articulate palpable pain in 25.86% also was peculiar to female sex. While the mandibular deflection was present in 68.18% had direct relation to male sex, and with and average age of 34.86 years old. The limited bucal opening stay significant relationed to DTM by 67.77% and to average age of 32.77 years old for women and 38.80 years old for men. Finally the persons with condilar position of two lock arcs, 99.10% had 15.67 times more probability of present a DTM.